A Tale of Two Crowds: Public Engagement in Plankton Classification - Robinson, Kelly L.; Luo, Jessica Y.; Sponaugle, Su; Guigand, Cedric; Cowen, Robert K. (Frontiers in Marine Science, 2017)
‘Big data’ are becoming common in biological oceanography with the advent of sampling technologies that can generate multiple, high-frequency data streams. Given the need for ‘big’ data in ocean health assessments and ecosystem management, identifying and implementing robust and efficient processing approaches is a challenge for marine scientists. Using a large plankton imagery data set, we present two crowd-sourcing approaches applied to the problem of classifying millions of organisms. The first used traditional crowd-sourcing by asking the public to identify plankton through a web-interface. The second challenged the data science community to develop algorithms via an industry partnership. We found traditional crowd-sourcing was an excellent way to engage and educate the public while crowd-sourcing data scientists rapidly generated multiple, effective solutions. As the need to process and visualize large and complex marine data sets is expected to grow over time, effective collaborations between oceanographers and computer and data scientists will become increasingly important.